Clinical Practice Guideline for the Management of Candidiasis: 2016 Update by the Infectious Diseases Society of America - Pappas, Peter G.; Kauffman, Carol A.; Andes, David R.; Clancy, Cornelius J.; Marr, Kieren A.; Ostrosky-Zeichner, Luis; Reboli, Annette C.; Schuster, Mindy G.; Vazquez, Jose A.; Walsh, Thomas J.; Zaoutis, Theoklis E.; Sobel, Jack D. (Clinical Infectious Diseases, 2016)
Abstract. It is important to realize that guidelines cannot always account for individual variation among patients. They are not intended to supplant physician

Clinical Practice Guidelines for the Management of Cryptococcal Disease: 2010 Update by the Infectious Diseases Society of America - Perfect, John R.; Dismukes, William E.; Dromer, Francoise; Goldman, David L.; Graybill, John R.; Hamill, Richard J.; Harrison, Thomas S.; Larsen, Robert A.; Lortholary, Olivier; Nguyen, Minh‐Hong; Pappas, Peter G.; Powderly, William G.; et al. (Clinical Infectious Diseases, 2010)